RECYCLING DISCREDITED PEDAGOGIES - Kelebay, Yarema Gregory (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1994)
THE LONDON FILE: PAPERS FROM THE INSTITUTE OF EDUCATION, UNIVERSITY OF LONDON. London: The Tufnell Press, 1993. David Buckingham (Editor). CHANGING LITERACIES: MEDIA EDUCATION AND MODERN CULTURE. 28 pp., £3.95. Graham Haydon (Editor). EDUCATION AND THE CRISIS IN VALUES: SHOULD WE BE PHILOSOPHICAL ABOUT IT? 25 pp., £3.95. Clare Hake (Editor). PARTNERSHIP IN INITIAL TEACHER TRAINING: TALK AND CHALK 36 pp., £3.95. James Tooley (Editor). A MARKET-LED ALTERNATIVE FOR THE CURRICULUM: BREAKING THE CODE. 42 pp., £3.95.